Improving IPAS Learning Outcomes through Differentiated Instruction and Assembler Edu - Shofwatul Azkiya; Susilawati; Dewi Yulianawati (Universitas Muhammadiyah Purwokerto, 2025)
This study aims to analyze the implementation of differentiated instruction integrated with Assemblr Edu media to enhance student learning outcomes in IPAS (Integrated Science and Social Studies). The issue addressed is the limited accommodation of students' diverse abilities and learning styles, which leads to suboptimal achievement. Differentiated instruction is considered an adaptive pedagogical approach, and the use of Assemblr Edu is expected to support its innovative application. This Classroom Action Research (CAR) employed the Kemmis and McTaggart spiral model, conducted in two cycles involving 30 fourth-grade students at UPTD SDN 1 Weru. Data were collected through learning outcome tests, observation sheets, and documentation. Quantitative data were analyzed by calculating average scores and classical completeness percentages, while qualitative data were analyzed descriptively. The results show a significant improvement in student learning outcomes. The average score increased from 52 (pre-cycle) to 63 in Cycle I and 73 in Cycle II. Classical completeness improved from 26.67% in the pre-cycle to 40% in Cycle I and 83.33% in Cycle II, surpassing the success indicator of 75%. Observations also revealed increased student engagement and more effective teacher facilitation tailored to student needs. In conclusion, implementing differentiated instruction supported by Assemblr Edu effectively enhances learning outcomes by addressing diverse learning needs and fostering interactive learning. It is recommended that teachers adopt pedagogical strategies aligned with student characteristics and leverage educational technology to optimize learning goals.